The Satisfaction Congruency Theory: The Case of Sexual Satisfaction (Recoletos Multidisciplinary Research Journal, 2014)
The culture of putting primacy to pleasure and satisfaction is gaining headway not only in the Philippines but in the world as well. It is slowly building a counter culture to the Catholic beliefs that the missionary friars propagated. Religion taught the people that sex is sacred, and rendered it as taboo in this culture. In this paper, the dynamics of satisfaction congruency in human behavior is delved into using the axiomatic approach to theory development. Self evident truths are explored to form the base of the theory building process. The developed theory states that congruent satisfaction is dependent on whether or not there is satisfaction in each of the three phases of an act. Congruent satisfaction occurs when the individual is satisfied in all these three phases: antecedent/planning phase, concurrent/execution phase, and the consequent/evaluation phase. Dissatisfaction in any of the phases results in incongruency. This, in turn, will influence the quality of life of the individual.
Keywords: congruent satisfaction; sexual satisfaction; satisfaction